A prospective observational description of frequency and timing of antenatal care attendance and coverage of selected interventions from sites in Argentina, Guatemala, India, Kenya, Pakistan and Zambia. Issue 2 (December 2015) - Bucher, Sherri; Marete, Irene; Tenge, Constance; Liechty, Edward; Esamai, Fabian; Patel, Archana; Goudar, Shivaprasad; Kodkany, Bhalchandra; Garces, Ana; Chomba, Elwyn; Althabe, Fernando; Barreuta, Mabel; et al.
Abstract Background The Global Network for Women's and Children's Health Research is one of the largest international networks for testing and generating evidence-based recommendations for improvement of maternal-child health in resource-limited settings. Since 2009, Global Network sites in six low and middle-income countries have collected information on antenatal care practices, which are important as indicators of care and have implications for programs to improve maternal and child health. We sought to: (1) describe the quantity of antenatal care attendance over a four-year period; and (2) explore the quality of coverage for selected preventative, screening, and birth preparedness components. Methods The Maternal Newborn Health Registry (MNHR) is a prospective, population-based birth and pregnancy outcomes registry in Global Network sites, including: Argentina, Guatemala, India (Belgaum and Nagpur), Kenya, Pakistan, and Zambia. MNHR data from these sites were prospectively collected from January 1, 2010 – December 31, 2013 and analyzed for indicators related to quantity and patterns of ANC and coverage of key elements of recommended focused antenatal care. Descriptive statistics were generated overall by global region (Africa, Asia, and Latin America), and for each individual site. Results Overall, 96% of women reported at least one antenatal care visit. Indian sites demonstrated the highest percentage of women who initiated antenatal care during the first trimester. Women from the Latin American and Indian sites reported the highest number of at least 4 visits. Overall, 88% of women received tetanus toxoid. Only about half of all women reported having been screened for syphilis (49%) or anemia (50%). Rates of HIV testing were above 95% in the Argentina, African, and Indian sites. The Pakistan site demonstrated relatively high rates for birth preparation, but for most other preventative and screening interventions, posted lower coverage rates as compared to other Global Network sites. Conclusions Results from our large, prospective, population-based observational study contribute important insight into regional and site-specific patterns for antenatal care access and coverage. Our findings indicate a quality and coverage gap in antenatal care services, particularly in regards to syphilis and hemoglobin screening. We have identified site-specific gaps in access to, and delivery of, antenatal care services that can be targeted for improvement in future research and implementation efforts. Trial registration Registration at Clinicaltrials.gov (ID# NCT01073475)